Doping silicon to enhance the anti-corrosion and anti-wear abilities of chromium nitride coating in seawater. (20th November 2018) - Yang, Dongping; Chen, Hao; Ye, Yuwei; Wang, Chunting; Zhao, Haichao; Gong, Dirong
Abstract: To solve the friction and wear problem of mechanical part in seawater, we have contrastively researched the microstructure, mechanical, corrosion and tribological properties of CrN and CrSiN coatings, which were prepared by medium frequency magnetron sputtering technology using two Cr targets and one Si target. It confirmed that the grain size of CrSiN coating was reduced by 46.67% after Si was added into CrN matrix. In the meantime, the CrSiN coating owned a typical nanocrystallite/amorphous structure, which consisted of CrN crystal phase and Si3 N4 amorphous phase. Furthermore, the hardness, toughness and anti-corrosion ability of CrN coating were obviously enhanced by the addition of proper silicon. Compared with CrN coating, the CrSiN coating exhibited a smaller friction coefficient (COF) and wear loss at different normal loads and sliding frequencies, which could be ascribed to its low surface roughness, high adhesion strength, good toughness, strong anti-corrosion ability and the lubrication of transfer film, indicating its excellent service potential as a protective coating.